Isolation and in silico characterization of two anthocyanin transcripts CHS and F3H from calyx of Hibiscus sabdariffa L. VAR. UMKL - Roshani, Maryam (2015)
Flavonoids represent a large class of secondary metabolites. These compounds possess many pharmacological and nutritional properties that are beneficial to human, as well as performing important biological roles in the growth and development of plants.Anthocyanin is one of the most abundant and important flavonoids. The calyx of Hibiscus sabdariffa (roselle) is rich in anthocyanin and phenolic compounds. In spite of the importance of Chalcone synthase (CHS) and Flavonone 3-hydroxylase (F3H) genes in the biosynthesis of flavonoids in plants, these genes have not been investigated in roselle. In this study, the transcripts of HsCHS and HsF3H were isolated from the calyx of roselle for the first time. HsCHS transcript sequence with a total length of 1167 bp and HsF3H with the total length of 1107 bp were isolated using PCR approaches. In addition, the start and stop codons, poly-A signal, poly-A tail, 3´ UTR and 5´ UTR regions for both isolated transcripts were also identified using in-silico analyses. Several important domains were predicted in the HsCHS deduced amino acid sequence,including CHS-like, fabH, BcsA, Chal-sti-synt-N and Chal-sti-synt-C, which indicates that the isolated cDNA sequence is probably a CHS transcript belonging to the polyketide synthase family. On the other hand, predictions of 2OG-FeII_oxy,Isopenicillin N synthase-like, DIOXN and PLN02515 domains in HsF3H deduced amino acid sequence, supports that the isolated cDNA sequence is an F3H transcript related to the large gene family of 2-oxoglutarate-dependent dioxygenases (2-ODDs). BLAST and phylogenetic analyses predicted the putative functions of the isolated HsCHS in the of condensation reaction of one 4-coumaroyl-CoA with three acetate molecules to produce naringenin; whereas an involvement of the HsF3H in catalyzing the reaction that transforms naringenin to dihydrokaempferol. However, further investigations must be carried out to confirm the function of HsCHS and HsF3H. This study predicted the putative functions of the two central genes (CHS and F3H) governing the flavonoid pathway of H. sabdariffa, which leads to anthocyanin production. It has also provided primary evidences on the predicted structures of the HsCHS and HsF3H transcripts, which is critical for getting a deeper insight into understanding the function of these genes in roselle.